MULTIMEDIA PRINCIPLES AND ITS USAGE IN GEOMETRY TEACHING - Мubarakovа .М; Ataev B.K; Karymsakova A.ZH (Academic Journal of Physical and Chemical Sciences, 2019)
Nowadays multimedia offers exciting possibilities both for learners and teachers. To get the educational benefits of new educational technologies such as multimedia learning tools it is important to study principles of multimedia learning and to use them for designing multimedia instructional messages. The purpose of this article is to acquaint the reader with principles of multimedia learning which has been popularized by an American educational psychologist Richard E. Mayer. An idea of that principles is organization of sound, text and images on the screen. There are some examples of mistakes that geometry teachers can make on their multimedia lessons in the article and it shows how they can be corrected. It may be useful for geometry teachers to make their multimedia presentations more effective. Each principle of multimedia learning for designing presentations for geometry lessons is subject to further research. All beliefs about benefits of multimedia must be supported by research.